The Economic and Social Consequences of Gambling on the Tourism Industry in Macau - Wong, Weng U (2007)
Macau is known as the Eastern Monte Carlo, her main industry of gambling makes Macau a rapid economic expansion and brings Macau a lot of job opportunities. However, in recent years, crime and negative social impacts have increased as a result of this industry. Gambling making Macau's economic structure lopsided and fragile as well as bring a series of social problems to Macau. This dissertation illustrates both the positive and negative impacts that Macau's gambling industry is having on international inward tourism and the consequences of those impacts for the city's economy. A questionnaire survey was carried out to a research population of 113 and the results show that most of respondents possess a neutral attitude towards gambling in Macau. Although gambling brings some negative impacts to Macau, it is known a very important feature of Macau's economy. Therefore in somehow, it is unavoidable,'a necessary evil'. On the other hand, it is suggested that the government of the Macau should set up a special committee for more studies on the future development and management of gambling industry. By increasing competition in the region, creating its own gambling model, and building up more attractions based on its cultural and heritage relations are the ways that can Macau realistically achieve a better balance of markets for the long-term development of its tourism industry.